PENGARUH PELAKSANAAN PROMOSI JABATAN TERHADAP KEPUASAN KERJA KARYAWAN PTPN V PEKANBARU (STUDI KASUS KARYAWAN KANTOR PUSAT PTPN V PEKANBARU) - Norman Gultom; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the effect of the conduct promotions on employee job satisfaction PTPN V Pekanbaru. Promotion as an independent variable (X) has been formulated that is viewed from the aspect of honesty, discipline aspect, the aspect of job performance, loyalty aspects, educational aspects, aspects of leadership and communicative aspects. While employee satisfaction as the dependent variable (Y). This study was conducted on all employees of the Head Office PTPN V Pekanbaru 83 people.Data obtained from questionnaires and subsequently processed to then be tested using statistical analysis as a simple linear regression analysis, t test, and correlation analysis and determination using SPSS.The results showed that the results of hypothesis testing t greater than t table that is 14.098 > 1.66. This shows that the implementation of the promotion effect on employee job satisfaction. The magnitude of the effect of the implementation of the promotion on employee job satisfaction PTPN V Pekanbaru Head Office is at 71%.Keywords: Job Of Promotion, Employees Performance